PENGARUH TINGKAT SUKU BUNGA PERBANKAN TERHADAP REALISASI INVESTASI DI INDONESIA (PERIODE 2011-2020) - A. Ika Fahrika; Muhammad Abdi Buhasyim (Fakultas Ekonomi dan Bisnis Islam IAIN Bone, 2021)
This study aims to determine (1) the effect of banking interest rates on investment realization in Indonesia, (2) how much banking interest rates on investment realization in Indonesia,The data analyzed is secondary data with time series (2011-2020). The data analyzed is secondary data with time series (2011-2020). The research to be carried out is expo facto (research conducted after what is to be researched has occurred). In this study, researchers used a quantitative research approach. Judging from its nature, this research is an associative research, which is a study that aims to determine the relationship between two or more variables. The data analysis that will be used in this research is linear regression which aims to describe the relationship between banking interest rates and investment realization in Indonesia.The results of the study show that (1) interest rates have a negative and insignificant effect on investment realization in Indonesia. (2). The magnitude of the influence of bank interest rates on investmentraelization is 11.2% and the rest influenced by other variables.